SYNERGISTIC ANTICANDIDAL ACTIVITY OF TWO TERMINALIA SPECIES WITH POLYENE AND AZOLE GROUP OF ANTIBIOTICS AGAINST MULTIDRUG-RESISTANT CLINICAL ISOLATES OF CANDIDA - Rathod, Tejas; Padalia, Hemali; Chanda, Sumitra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of the present study was to evaluate synergistic anticandidal activity of two Terminalia species with polyene and azole group of antibiotics against multidrug-resistant clinical isolates of Candida. Methods: The synergistic effect of ethanol extract of leaf of Terminalia cattapa. and Terminalia chebula with six standard antibiotics, namely, amphotericin B, nystatin, fluconazole (FLC), ketoconazole (KT), clotrimazole (CC), and itraconazole (IT) was evaluated against the clinical isolates by disk diffusion assay. Results: The synergistic activity of the antibiotics with ethanol extract of T. chebula was better than with that of T. cattapa. T. chebula ethanol extract increased the anticandidal effect of azole antibiotics FLC and KT, while it had a less synergistic effect on CC and IT. Conclusion: Therefore, FLC/KT plus ethanol extract of T. chebula can be an interesting and alternative source of anticandidal agent against Candida species.